Palacio de Justicia de la ciudad de Córdoba - Armando, Armando (1999)
Por <GGMPU arquitectos>.
Keywords: GRAMATICA, SARA; MORINI, JORGE; PISANI, JOSE; URTUBEY, EDUARDO; EDIFICIOS JUDICIALES; CORDOBA; ARGENTINA; EDIFICIOS PUBLICOS